Immunoproteomics of processed beef proteins reveal novel galactose‐α‐1, 3‐galactose‐containing allergens. Issue 10 (28th July 2014) - Apostolovic, D.; Tran, T. A. T.; Hamsten, C.; Starkhammar, M.; Cirkovic Velickovic, T.; van Hage, M.
Abstract Background Red meat allergy presents a novel form of food allergy with severe delayed allergic reactions where IgE antibodies are directed against the carbohydrate α‐Gal epitope. Food preparation and processing can influence the allergenicity of proteins. The aim of this study was to characterize the proteomic profile of different beef preparations and to investigate their α‐Gal reactivity and potential allergenicity. Methods Extracts from raw, boiled, fried, and medium rare prepared beef were assessed by 2D PAGE for the comparison of protein profiles. IgE‐binding proteins were identified using immunoblot‐coupled proteomic analysis using sera from red meat‐allergic patients. Presence of the α‐Gal epitope was verified using anti‐α‐Gal antibody and IgE inhibition immunoblot with α‐Gal. Results Multiple IgE‐binding proteins were detected in the different beef preparations, many of which were also recognized by the anti‐α‐Gal antibody. Protein spots reacting with IgE in patient sera were analyzed by MS/MS, resulting in identification of 18 proteins with high identification scores. Seven of the 18 beef allergens identified using meat‐allergic patient sera were also recognized by the anti‐α‐Gal monoclonal antibody, and four of them were stabile to thermal treatment. Furthermore, a dose‐dependent inhibition of red meat‐allergic patients' IgE to beef by α‐Gal was demonstrated. Conclusions We show that the α‐Gal epitope is commonly present in IgE‐reactive beef proteins recognized by meat‐allergic patients. Seven novel α‐Gal‐containing IgE‐binding proteins were identified, of which four were stable to heat treatment. Thus, the allergenicity of red meat proteins is preserved even upon different thermal cooking.